Analisis Pembelajaran E-learning pada Subtema Tubuhku - Ukhti Salamah; Filia Prima Artharina; Mila Karmila (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The educational process that relies on face-to-face only is traditional teaching system that runs slowly and does not keep pace the times. Since the discovery of multimedia communication media, appropriate information and communication technology the basis for cutting-edge learning. Ideal demands of the 2013 Curriculum use ICT to improve the efficiency and effectiveness of learning. Observation results show the implementation e-learning at SDN 01 Kejambon is not optimal, SD and a source information. Teachers not been fully able to create teaching materials on internet, interactive forums in cyber world, or test using E-learning system. The results interviews with students showed that some students did not understand E-learning-based learning well. Responding these problems, inecessary to conduct study of implementation analysis to determine the implementation of e-learning in elementary schools.